BUCCAL MUCOADHESIVE FILMS - G. D., SINDHU; NALLAGUNTLA, LAVANYA; KULKARNI, GURURAJ S. (International Journal of Current Pharmaceutical Research, 2021)
The buccal route of administration has many advantages, including gastrointestinal bypass surgery and first pass through the liver. The mucoadhesive membrane is a retention dosage form that can release the drug directly into the biological matrix. Cheek technology has proven to be an advanced alternative to other traditional devices. The type of drug delivery system. This is a mature technology for systemic administration of active pharmaceutical ingredients [API]. In addition, due to their small size and thinness, these films improve patient compliance. Over the past decade, because it is a promising delivery alternative for multiple therapeutic categories, including peptides, vaccines and nanoparticles. Mucosal adhesions are currently explained by six theories: electronics, adsorption, wettability, diffusion, degradation and mechanics. Various in vitro and in vivo techniques are suggested. Study its mechanism. This study includes an overview of the mechanisms and theories of mucosal adhesion, and introduces the most commonly used methods. The "film casting method" involves casting an aqueous solution and/or organic solvent to produce a film suitable for the application route. The determination of key properties such as mucosal adhesion strength, uniformity of active ingredient content and permeability are important research areas in the field of buccal membrane design.